2019
DOI: 10.1097/qai.0000000000002156
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Biomarker-Confirmed Alcohol Use Among Pregnant Women Living With HIV in South Africa and Uganda

Abstract: Background: Alcohol use is common among people living with HIV and particularly harmful during pregnancy. However, objective data on alcohol use in pregnant women living with HIV (WLWH) are lacking. In areas with high levels of alcohol use generally, such as South Africa and Uganda, these data are needed to inform interventions. Methods: Pregnant and nonpregnant, antiretroviral therapy-naive WLWH were recruited from outpatient clinics in South Africa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 65 publications
2
30
1
Order By: Relevance
“…Next, alcohol use, number of sex partners, and IPV were self-reported and participants might have underestimated or forgotten their true behaviors, potentially leading to reduced accuracy of findings. However, it is encouraging to note that our alcohol use findings are similar to previous studies, some of which used biomarkers [ 7 ]. Third, our analysis is among women who self-reported as pregnant and our sample included some women who were not pregnant and excluded women who were unknowingly pregnant.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Next, alcohol use, number of sex partners, and IPV were self-reported and participants might have underestimated or forgotten their true behaviors, potentially leading to reduced accuracy of findings. However, it is encouraging to note that our alcohol use findings are similar to previous studies, some of which used biomarkers [ 7 ]. Third, our analysis is among women who self-reported as pregnant and our sample included some women who were not pregnant and excluded women who were unknowingly pregnant.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the prevalence of self-reported drinking during pregnancy in Rakai, Uganda, was over three times higher than the global average of alcohol use among pregnant women [ 3 ], higher than previous studies conducted among pregnant women in other regions of Uganda [ 6 , 7 ], but lower than the prevalence of alcohol use among non-pregnant women in Rakai, Uganda [ 8 ]. Correlates of alcohol use during pregnancy were Catholic religion, occupation in a restaurant or bar, higher numbers of past year sex partners, having a partner who drank before sex in the past 12 months, and experiencing IPV.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In Mpumalanga Province, South Africa, self-reported adherence to ART was 69% among pregnant WLWH [11] and in Zimbabwe, only 40% of women were taking at least 95% of ART by pill count one year postpartum [12]. Qualitative data from sub-Saharan African sites suggest that adherence challenges for pregnant and postpartum WLWH relate to structural barriers to care, community and healthcare stigma, medication side effects, depression, substance use and the overwhelming challenges of poverty, gender norms, and life with a newborn [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO does not provide detailed advice on how to screen pregnant women, but screening methods based on questionnaires are mentioned as an alternative. However, self‐reporting has been shown to underestimate alcohol use and to be unreliable among pregnant women due to poor memory, social stigma, and fear of child welfare interventions (Ferraguti et al, 2017; Lange et al, 2017; Raggio et al, 2019).…”
mentioning
confidence: 99%